Genotype-Phenotype Relationship in Hereditary Haemochromatosis - Ayres, Lachlan; Jayasekeran, Vanoo; Olynyk, John (John Wiley & Sons, Inc, 2013)
The majority of patients of northern European descent with Hereditary Hemochromatosis are homozygous for the C282Y mutation in the HFE gene product. A significant proportion of patients with this genotype have elevated iron indices, however most will not develop symptoms or organ damage. Age, gender and alcohol are the key factors known to influence this wide variation in clinical penetrance. We describe the three stages of disease ranging from genetic abnormality-only through to overt disease, and review the other factors which modify the genotype-phenotype relationship. Algorithms for use in clinical practice are included to aid clinicians in diagnosis, risk stratification and treatment.